The Effect of Product Quality and Modern Packaging Training on the Competitiveness of Salted Fish Products in the Belawan Coastal Area - Ade Adryana Putri Sitanggang; Ardina Ella Putri Siregar; Nalom Siagian; Kepler Sinaga (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of product quality and modern packaging training on the competitiveness of salted fish products in the coastal area of Belawan. This research employed a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Research data were collected through questionnaires distributed to 100 salted fish business actors as respondents and were analyzed using measurement model and structural model testing to identify relationships among variables. The results indicate that product quality has a positive and significant effect on competitiveness, with a path coefficient of 0.398 and a p-value < 0.05. In addition, modern packaging training also has a positive and significant effect on competitiveness, with a path coefficient of 0.411 and a p-value < 0.05.The R-square value of 0.426 indicates that product quality and modern packaging training explain 42.6% of the variance in competitiveness, while the remaining variance is explained by other variables outside this study. The findings emphasize the importance of improving product quality and strengthening modern packaging skills as strategic efforts to develop salted fish businesses in order to remain competitively sustainable amid evolving market dynamics. This study is expected to serve as a practical reference for business actors and policymakers.